Manajemen Risiko Pelaksanaan Proyek Peningkatan Jalan Kota Denpasar Dan Dampaknya Terhadap Lingkungan - Dewa Ayu Trisna Adhiswari Wedagama; Irma Suryanti (Dinasti Research, 2024)
Good roads are one of the important things in the world of transportation, especially in Denpasar City. This encourages improvements to road infrastructure in Denpasar City through road management activities including road maintenance and improvement. Road improvement construction work is the work that has the most risks and impacts on the surrounding environment during the road improvement project process. This research aims to identify and mitigate risks in road improvement construction work in Denpasar City. The method used in the research was interview methods with respondents involved in road construction projects in Denpasar City. The risk assessment is carried out after receiving answers from respondents, this aims to measure the dominant risks that exist. The risk mitigation process and risk ownership will be held accountable by the project owner as well as contractors, supervisory consultants, and planning consultants. The results of the research were 30 risks found in road improvement projects in Denpasar City with the sources being the environment (14.3%), politics (5.8%), planning (8.5%), economy (5.7%), natural (8.52%), technical (22.08%), human (8.5%), criminal (6.7%), safety (5.7%), project (14.2%). From the results of this analysis, risks in the technical, environmental, and project categories have the highest percentage. The environmental impact factor is also considered in this construction work because it is ranked second after technical risk. This encourages the implementation of risk management in every road improvement project activity in the following years, to create appropriate handling strategies that do not harm the environment.